Morphological assessment of pollen foraged by Apis dorsata fabricius and spatial distribution of pollen sources using remote sensing in Marang, Terengganu, Malaysia - Ibrahim, Izzat Fatanah (2012)
Apis dorsata is one of the important honeybee species in tropical and subtropical regions that forage on various plants including herbs, grasses, forest trees and plantation trees. However, information on the favored bee plants in the study area in terms of identity, quantity and mapping of various pollen sources found in pollen cells collected by Apis dorsata bees is lacking. The objectives of this study were: i)to identify pollen source and determine the pollen type and number preserved in pollen cells, ii) to develop a pollen atlas of selected important foraging plants for Apis dorsata, and iii) to map the distribution of the major bee plants in Marang, Terengganu. For the first objective, the pollen cell samples from twenty one different colonies of Apis dorsata combs were collected, identified and quantified based on several reference materials. In this study, a total of twelve different pollen types were identified in the samples, which are: Acacia sp., Durio zibethinus, Elaeis guineensis, Ixora sp., Cocos nucifera, Mikania cordata, Mimosa pudica, Melaleuca cajuputi, Garcinia sp., Mimusops elengi, Avicennna alba and Moringa pterygosperma. The two most commonly found pollen types were Elaeis guineensis (54%) and Mimosa pudica (29%). For the second objective, a pollen atlas was developed. Pollen sizes were in the range of 8-9 μm x 38-40 μm, comprising five different shape classes. In this study, inaperturate granulum pollen grains were observed in Ceiba petandra (Bombacaceae) and Garcinia hombroniana (Guttiferea), while rugulae grains were found in Mangifera indica (Anacardiaceae). Pantoporate, syncolpate, and pericolpate pollen grains with reticulum to microreticulate exine patterns occurred in Acacia auriculiformis (Fabaceae), Melaleuca cajuputi (Myrtaceae) and Ixora congesta (Rubiaceae). Elaeis guineensis has trichotomosulcate pollen grains with a microreticulate sexine. Pantocolpate areola pollen was found in Mimosa pudica (Mimosaceae), while granulum pollen was observed in Cocos nucifera (Palmae). Anacardium occidentale (Anacardiaceae) showed a disulcate grain with a striate sexine pattern. Pollen grains of Averrhoa carambola (Oxalidaceae) and Dimorcarpus longan (Sapindaceae) were tricolpate, and fossulate perforate to striate perforate.For the third objective, the acquired SPOT 5 satellite imagery was enhanced, classified and vectorized using ENVI software for the purpose of bee plant mapping. Using image classification, the bee plants were categorized into six classes. Ten plots of 10 x 10 m size for each bee plant classes were determined using a randomized sampling technique. Results showed that Melaleuca cajuputi covered 2,398.8 ha (5.5%), Acacia sp. 11,377.8 ha (25.9%), Elaeis guineensis 19745.1 ha (44.9%), non vegetation 4,647.2 ha (10.6%), water bodies 973.5 ha (2.2%) and cloud/haze/shadow 4830.5 ha (10.6%). The overall classification accuracy was 91.5% and the Kappa coefficient was 0.8.